EFFECTS OF CHILDHOOD OBESITY IN BRAZIL: A MULTIPROFESSIONAL ANALYSIS IN PRIMARY HEALTH CARE - Soares, Maria da Silva (2024)
Overweight and obesity affected around 340 million children and adolescents worldwide in 2016. In this sense, as obesity is a chronic disease, the factors related to this public health issue must be understood, including: sedentary lifestyle, low socioeconomic power and access to the health system. The present study aimed to understand the main approaches to preventing and managing obesity in primary health care. A narrative review of the literature was carried out, using the descriptors in the PubMed, SciELO and Periódico Capes databases, which obtained 342 articles, 31 of which were chosen to form the basis of this review. According to the multifactorial origin of obesity, current studies have revealed the relevance of therapeutic interventions in several areas, including primary care, family support, school environment, technologies, drug or surgical treatments. Additionally, the difficulties faced in preventing and adequately treating obesity in childhood are evident. Therefore, interdisciplinary monitoring in partnership with schools and families becomes essential, aiming to promote the health of young people and children, preventing obesity in adulthood and also preserving mental health, in addition to preventing diseases related to obesity and its consequences. complications.